PENGARUH METODE FONIK BERBANTUAN MEDIA FLASH CARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA SEKOLAH DASAR - Dahlani, Awaliyah; Annisa Siti Fauziah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the fact that many second-grade elementary school students still experience reading difficulties. This study aims to examine the effect of the phonics method assisted by flash card media on students' early reading skills. The phonics method supports understanding of the letter-sound relationship, while flash cards enhance interest and participation in learning. This research employed a quantitative approach using a quasi- experimental design with a nonequivalent control group. The study involved 22 second-grade students at SD Negeri Panyingkiran III, selected through purposive sampling. The instrument used was an early reading test measured through indicators such as punctuation use, speech clarity, pronunciation, and intonation. Data analysis was conducted using SPSS version 27, including the Shapiro-Wilk test for normality, Levene’s test for homogeneity, t-test or Mann-Whitney test, and effect size analysis.The results showed a significant impact, with a significance value of 0.001 (< 0.05). The experimental group’s average post-test score of 73.82 was higher than the control group's 55.68. The effect size value of -2.177 indicated a very strong influence.